A 1.8-V 2.4/5.15-GHz dual-band LC VCO in 0.18-μm CMOS technology - Jia, Lin (2009)
A dual band, fully integrated, low phase-noise and low-power voltage-controlled oscillator (VCO) operating at the 2.4-GHz industrial scientific and medical band and 5.15-GHz unlicensed national information infrastructure band has been demonstrated in an 0.18-um CMOS process. At 1.8-V power